Analysis of the Effect of Financial Ratios on ROA (Return on Asset) at National Private Commercial Banks in Indonesia - Windri, Yenni Permata (Arthavidya Jurnal Ilmiah Ekonomi, 2021)
Abstract Banks are business entities that collect funds from the public in the form of deposits and redistribute them in the form of loans and / or other forms in order to improve the standard of living of many people. Performance is an illustration of the condition of a bank, regarding the good and bad condition of a bank that reflects work performance in a certain period. Financial ratios can help business people, government parties and other users of financial statements in assessing the financial condition and performance of the bank. This study aims to see the effect of financial ratios, namely Loan to Deposit Ratio (LDR), Non Performing Loans (NPL) and BOPO to the performance of National Private Commercial Banks, namely Return on Assets (ROA). The sampling method uses purposive sampling, which uses samples with certain criteria, the samples used in this study are three national private commercial banks namely Bukopin Bank, Mega Bank and OCBC NISP Bank. The data analysis method used is multiple linear regression analysis. Partial test results show that the LDR partially has a non-significant positive effect on ROA in National Private Commercial Banks for the period 2010 to 2013. NPLs partially have a non-significant negative effect on ROA at National Private Commercial Banks for the period from 2010 to 2013 and BOPO partially had a significant negative effect on ROA in National Private Commercial Banks for the period 2010 to 2013. Keywords: Loan to Deposit Ratio, Non Performing Loan, Operational Costs to Operating Income